A look at geography teaching in the early years of fundamental education (Research, Society and Development, 2020)
Elementary School I comprises from the 1st to the 5th year, its target audience is children from 6 to 10 years old and is a cycle in which the curricular components are taught by teachers with a degree in Pedagogy. In this context, such teachers are responsible for promoting activities in different areas, whether in the field of literacy and literacy, logical-mathematical reasoning or the initial notions of History, Natural Sciences and Geography. The aim of this study is to analyze some aspects of Geography teaching in the early years of elementary school and the role assumed by teachers responsible for working with geographic content at this stage of education. With regard to the methodology used, it can be said that this is a qualitative research, which adopted documentary and bibliographic analysis as methodological procedures. The study showed that the teachers responsible for classes in Elementary School I, must find a way to work with their students so that they know the world, the place where they live and their relationship with space. Therefore, in the pedagogical practices aimed at students in the early years of elementary school, it is essential that the teacher gives due attention to immediate and concrete experiences of the children.